"You'll find no smoking gun": challenging the police narrative in the aftermath of the Hillsborough disaster - Scraton, Phil (Introduction to policing research, 2024)
The 15th April 1989 was a warm, sunny day in Sheffield. In fine spirits, 54,000 football fans arrived at Hillsborough, Sheffield to watch their teams, Liverpool and Nottingham Forest, play in the FA Cup Semi-Final. Within an hour of their arrival a crush occurred inside the stadium resulting in the death of 97 men women and children. In the aftermath I led the Hillsborough Project, an independent research study funded by the Liverpool City Council (Coleman et al.1990; Scraton et al.1995). My subsequent in-depth research focused initially on the experiences of survivors and the bereaved, institutional failures by the police and other authorities, and the inadequacies of the official investigations and inquiries (Scraton 1999). In 2009, a sustained campaign by families and survivors, resulted in my appointment to an independent panel to research all available documentation and audio-visual material. Following analysis of many thousands of documents accessed from all organisations involved we published 153 findings. I was primary author of its detailed report (HIP 2012). It revealed previous investigations, inquiries and reviews had been fundamentally flawed. ‘Hillsborough’ has come to represent institutional denial of responsibility by all agencies involved and police corruption of evidence. What follows examines the SYP’s role and the West Midlands Police (WMP) investigation – its evidence-gathering for the Home Office Inquiry, the Coroner and the Independent Police Complaints Commission (IPPC). It includes my revelations of the alteration of police statements (Scraton 1999), the HIP findings that led to the second inquests (2013–2016) and criminal prosecutions (2019–2021).